Hemostatic Alginate/Nano-Hydroxyapatite Composite Aerogel Loaded with Tranexamic Acid for the Potential Protection against Alveolar Osteitis - Mai El Halawany; Randa Latif; Mohamed H. H. AbouGhaly (MDPI AG, 2022)
Wound control in patients on anticoagulants is challenging and often leads to poor hemostasis. They have a higher tendency to develop alveolar osteitis after tooth extraction. The application of a hemostatic dressing that has a high absorbing capacity and is loaded with an antifibrinolytic drug could help in controlling the bleeding. Alginate/nano-hydroxyapatite (SA/Nano-HA) composite aerogels loaded with tranexamic acid (TXA) were prepared. Nano-HA served as a reinforcing material for the alginate matrix and a source of calcium ions that helps in blood clotting. It influenced the porosity and the water uptake capacity. TXA release from SA/Nano-HA aerogels showed a biphasic profile for up to 4 h. Blood coagulation studies were performed on human whole blood. The TXA-loaded aerogel significantly reduced the clotting time by 69% compared to the control (p < 0.0001). Recalcification time was significantly reduced by 80% (p < 0.0001). Scanning electron microscopy analysis revealed the porous nature of the aerogels and the ability of the optimum aerogel to activate and adhere platelets to its porous surface. The cell migration assay showed that there was a delay in wound healing caused by the TXA aerogel compared to the control sample after treating human fibroblasts. Results suggest that the developed aerogel is a promising dressing that will help in hemostasis after tooth extraction.